The Shadow of Legal Pluralism in Indonesian Islamic Courts: Child and Spousal Maintenance - van Huis, Stijn Cornelis (UI Scholars Hub, 2025)
This paper is inspired by Franz von Benda-Beckmann’s notion of “bargaining in the shadow of legal pluralism” and applies this notion to spousal and child maintenance negotiations that take place between judges, husbands and wives within divorce processes at Indonesian Islamic courts. I will argue that in the context of Muslim family law practice in Indonesia, the legal plural situation does not only influence out-of-court negotiations, but formal legal processes within the Islamic courts as well. It follows Keebet von Benda-Beckmann’s example in analyzing the legal plural dynamics of women’s claiming process comprehensively, by investigating the interconnectedness of the pre-trial, trial and post-trial phases of the pos-divorce maintenance claiming process. I will show how the non-state normative frameworks that dominate claiming processes in the pre-trial and post-trial phases cast their shadow over judicial proceedings in the court room. The paper concludes that the weak normative and persuasive force that maintenance court orders have within the non-state normative frameworks of local communities correlates with how Islamic courts treat women’s post-divorce maintenance claims. The shadow of legal pluralism in this case means that women have a disadvantaged bargaining position vis-à-vis their husband when they attempt to claim their statutory post-divorce rights through a court process.